L-alanyl-L-glutamine ingestion maintains performance during a competitive basketball game - Hoffman, J. R.; Williams, D. R.; Emerson, N. S.; Hoffman, M. W.; Wells, A. J.; McVeigh, D. M.; McCormack, W. P.; Mangine, G. T.; Gonzalez, A. M.; Fragala, M. S. (Journal of the International Society of Sports Nutrition, 2012)
The purpose of this study was to examine the efficacy of L-alanyl-L-glutamine (AG) ingestion on basketball performance, including jump power, reaction time, shooting accuracy and fatigue. Methods Ten women (21.2 +/- 1.6 years; height: 177.8 +/- 8.7 cm; body mass: 73.5 +/- 8.0 kg), all scholarship NCAA Division I basketball players, volunteered for this study. Subjects participated in four trials, each consisting of a 40-min basketball game with controlled time-outs for rehydration. During the first trial (DHY) subjects were not allowed to rehydrate, and the total weight lost during the contest was used to determine fluid replenishment during the subsequent three trials. During one trial subjects consumed only water (W), while during the other two trials subjects consumed the AG supplement mixed in water using either a low dose (1 g per 500 ml) (AG1) or high dose (2 g per 500 ml) (AG2) concentration. All data assessed prior to and following each game were converted into a [increment] score (Post results - Pre results). All performance data were then analyzed using a one-way repeated measures analysis of variance. Results During DHY subjects lost 1.72 +/- 0.42 kg (2.3%) of their body mass. No differences in fluid intake (1.55 +/- 0.43 L) were seen between rehydration trials. A 12.5% (p = 0.016) difference in basketball shooting performance was noted between DHY and AG1 and an 11.1% (p = 0.029) difference was seen between AG1 and W. Visual reaction time was significantly greater following AG1 (p = 0.014) compared to DHY. Differences (p = 0.045) in fatigue, as determined by player loads, were seen only between AG2 and DHY. No differences were seen in peak or mean vertical jump power during any trial. Conclusion Rehydration with AG appears to maintain basketball skill performance and visual reaction time to a greater extent than water only.